2016
DOI: 10.1175/bams-d-15-00029.1
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Radar Analysis of Triple Eyewalls in Typhoon Usagi (2013)

Abstract: 23Strong tropical cyclones often undergo eyewall replacement cycles that is accompanied 24 with concentric eyewalls and/or rapid intensity changes while the secondary eyewall contracts 25 radially inward and eventually replaces the inner eyewall. To the best of our knowledge, the only 26 documented partial/incomplete tertiary eyewall has been mostly inferred from two-dimensional 27 satellite images or one-dimensional aircraft flight-level measurements that can be regarded as 28indirect and tangential. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…While the secondary eyewalls are subject of interest in the TC research, TC with triple eyewalls is known to exist (McNoldy, 2004;Tsujino et al, 2017;Zhao et al, 2016). We extend the objective method of to the identification of triple eyewalls.…”
Section: Methodsmentioning
confidence: 99%
“…While the secondary eyewalls are subject of interest in the TC research, TC with triple eyewalls is known to exist (McNoldy, 2004;Tsujino et al, 2017;Zhao et al, 2016). We extend the objective method of to the identification of triple eyewalls.…”
Section: Methodsmentioning
confidence: 99%
“…The outer eyewall continued to weaken in the weakening phase and was replaced by the outermost rainbands in the dissipation phase, whereas the inner eyewall remained unchanged. Aircraft (McNoldy 2004;Sitkowski et al 2011) and radar (Zhao et al 2016) observations have determined that some CE TCs (e.g., Hurricanes France 2004 and Ivan 2004) had triple wind maxima. This N-ERC-Multiple pattern might be related to the triple wind maxima configuration: the inner wind maximum corresponds to the inner eyewall, the middle maximum forms when the CE forms, and the outer maximum is related to spiral rainbands that evolve into the outer eyewall.…”
Section: N-erc-multiple Pattern (2 Cases)mentioning
confidence: 99%
“…Based on aircraft and satellite observations, Hawkins and Helveston (2008) indicated that approximately 70 % of intense TCs (maximum wind speed > 50 m s −1 ) between 1997 and 2006 in the North Atlantic, 50 % in the eastern Pacific, and 80 % in the western Pacific had CE structures. Moreover, triple eyewall configurations were observed (McNoldy 2004;Tsujino et al 2017;Zhao et al 2016) in Hurricane Juliette (2001), and typhoons Bolaven (2012) and Usagi (2013). It is considered that a stronger TC often has a higher probability of having a CE configuration (Kossin and Sitkowski 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the convective activity related to the generation of the eddy kinetic energy is not fully addressed. Some studies focused on spiral rainbands because the SEF generally starts from convective rainbands (Houze, 2007;Zhao et al, 2008Zhao et al, , 2016Kossin and Sitkowski, 2009). When the rainband outside the eyewall is enhanced by adding a large diabatic heating rate to the rainband in a numerical simulation, the TC can experience the SEF (Wang, 2009).…”
Section: Introductionmentioning
confidence: 99%